ANALISIS SIKAP PEMILIH MUDA TERKAIT ISU KAMPANNYE HITAM DI MEDIA SOSIAL SELAMA PROSES KAMPANYE CALON PRESIDEN DAN WAKIL PRESIDEN PADA PEMILIHAN UMUM 2019 : (Studi Kasus Pada Pemilih Muda Alumni SMAN 46 Jakarta Selatan Angkatan 2019) - Befinka Figiel Yonas (2024)
This research aims to determine the attitudes of young voters from the Class of 2019 SMAN 46 South Jakarta Alumni towards the issue of black campaigns on social media during the campaign process for presidential and vice presidential candidates in the 2019 General Election. Since the implementation of the multiparty system in Indonesia, parties have competed with each other to fight for power. carrying out a black campaign in the election. Black campaigns containing hoax issues have an indirect impact on young voters. This research examines the attitudes of young voters towards black campaign issues on social media in the 2019 presidential election using qualitative research methods with primary and secondary data sources. Data collection techniques were interviews and literature studies in the form of books, news and previous research journals that were relevant to this research. Pawelec's Deepfakes Information and Democracy theory is used to explain the attitudes of young voters towards the issue of black campaigning on social media in the 2019 Presidential Election. The results of the research show that the impact of deepfakes or information manipulation as a form of black campaigning has an impact in making young voters who are alumni of SMAN 46 Jakarta no longer trust any information. only what is seen or heard on social media and suppresses the number of young voters, alumni of SMAN 46 Jakarta, by speculating that the campaign tends to be negative and has the impact that new voters, alumni of SMAN 46 Jakarta, do not have a strong preference for one of the candidates, becoming embarrassed or disappointed.